THU0121 Low Disease Activity and ACR70-Response Is Associated with The Inhibition of Periarticular Bone Loss in Rheumatoid Arthritis Patients Treated with Certolizumab Pegol plus Methotrexate. (15th July 2016) - Pfeil, A.; Nussbaum, A.; Jung, C.; Reinhardt, L.; Oelzner, P.; Malich, A.; Böttcher, J.; Wolf, G.
Abstract : Background: Anti-TNF treatment with certolizumab pegol is an effective therapy in patients with rheumatoid arthritis (RA). Objectives: The aim of this study, based on a post-hoc analysis of the data set used in the RAPID 1 trial (1), focuses on the associations between metacarpal bone mineral density as estimated by Digital X-ray Radiogrammetry and disease activity as well as ACR70-Response in RA patients treated with certolizumab pegol plus methotrexate (CZP+MTX). Methods: The post-hoc analysis of the RAPID 1 trial evaluates a total of 345 patients: 34 patients who received placebo plus methotrexate (PBO+MTX), 155 patients who received CZP 200 mg (every two weeks) plus MTX and 156 patients who received CZP 400 mg (every two weeks) plus MTX. All patients underwent x-rays of the hand at baseline and week 52 as well as computerized calculations of bone mineral density (BMD) by DXR (2). ACR70-response was evaluated. Results: The highest CRP reduction was observed for patients treated with CZP 400 mg + MTX (-63.6%, p<0.05) and CZP 200 mg + MTX (-55.9%, p<0.05) compared to the PBO+MTX (-24.7%, p<0.05). An equal constellation was revealed regarding the DAS28-CRP (CZP 400 mg + MTX: -50.5%, p<0.05; CZP 200 mg + MTX: -49.3%, p<0.05 and PBO + MTX: -31.3%, p<0.05). In accordance with these results, DXR-BMD showed a minor significant bone loss for the treatment groups undergoing therapy with CZP 400 mg + MTX and CZP 200 mg + MTX with -1.1% (p<0.05) versus -1.3% (p<0.05), and an advanced periarticular metacarpal bone loss of -5.5% (p<0.05) in the PBO+MTX. The patients treated in the small PBO+MTX group revealed no significant ACR70-Response. Both CZP+MTX groups revealed a significant ACR70-Response. In the case of ACR70-Response no significant change of the DXR-BMD was observed. Conclusions: The study highlights that patients treated with CZP+MTX showed a high reduction of CRP and DAS28-CRP in association to a less accentuated periarticular bone loss as estimated by DXR in comparison to patients treated with PBO+MTX. Additionally, patients with ACR70-Response revealed no periarticular demineralisation. The reduced periarticular demineralization functions as a surrogate marker for the bone protective effects of certolizumab pegol. References: Keystone E, Heijde Dv, Mason D Jr, et al. Certolizumab pegol plus methotrexate is significantly more effective than placebo plus methotrexate in active rheumatoid arthritis: findings of a fifty-two-week, phase III, multicenter, randomized, double-blind, placebo-controlled, parallel-group study. Arthritis Rheum 2008;58:3319–29. Pfeil A, Haugeberg G, Hansch A, et al. Value of digital X-ray radiogrammetry in the assessment of inflammatory bone loss in rheumatoid arthritis. Arthritis Care Res (Hoboken) 2011;63:666–74. Disclosure of Interest: None declared